The Cytotoxic Activity of Dammarane-Type Triterpenoids Isolated from the Stem Bark of Aglaia cucullata (Meliaceae) - Purnama; Kindi Farabi; Dudi Runadi; Hadi Kuncoro; Desi Harneti; Nurlelasari; Tri Mayanti; Mohamad Nurul Azmi; Sofa Fajriah; Unang Supratman (Molecules, 2023)
The Aglaia genus, a member of the Meliaceae family, is generally recognized to include a number of secondary metabolite compounds with diverse structures and biological activities, including triterpenoids. Among the members of this genus, Aglaia cucullata has been reported to have unique properties and thrives exclusively in mangrove ecosystems. This plant is also known to contain various metabolites, such as flavaglines, bisamides, and diterpenoids, but there are limited reports on the isolation of triterpenoid compounds from its stem bark. Therefore, this research attempted to isolate and elucidate seven triterpenoids belonging to dammarane-type (1–7) from the stem bark of Aglaia cucullata. The isolated compounds included 20S,24S-epoxy-3α,25-dihydroxy-dammarane (1), dammaradienone (2), 20S-hydroxy-dammar-24-en-3-on (3), eichlerianic acid (4), (20S,24RS)-23,24-epoxy-24-methoxy-25,26,27-tris-nor dammar-3-one (5), 3α-acetyl-cabraleahydroxy lactone (6), and 3α-acetyl-20S,24S-epoxy-3α,25-dihydroxydammarane (7). Employing spectroscopic techniques, the chemical structures of the triterpenoids were identified using FTIR, NMR, and HRESITOF-MS. The cytotoxic activity of compounds 1–7 was tested with the PrestoBlue cell viability reagent against MCF-7 breast cancer, B16-F10 melanoma, and CV-1 normal kidney fibroblast cell lines. The results displayed that compound 5 had the highest level of bioactivity compared to the others. Furthermore, the IC50 values obtained were more than 100 μM, indicating the low potential of natural dammarane-type triterpenoids as anticancer agents. These findings provided opportunities for further studies aiming to increase their cytotoxic activities through semi-synthetic methods.